Prokaryotes of renowned Karlovy Vary (Carlsbad) thermal springs: phylogenetic and cultivation analysis - Smrhova, Tereza; Jani, Kunal; Pajer, Petr; Kapinusova, Gabriela; Vylita, Tomas; Suman, Jachym; Strejcek, Michal; Uhlik, Ondrej (Environmental microbiome, 2022)
BACKGROUND: The extreme conditions of thermal springs constitute a unique aquatic habitat characterized by low nutrient contents and the absence of human impacts on the microbial community composition. Thus, these springs may host phylogenetically novel microorganisms with potential use in biotechnology. With this hypothesis in mind, we examined the microbial composition of four thermal springs of the world-renowned spa town of Karlovy Vary (Carlsbad), Czechia, which differ in their temperature and chemical composition. RESULTS: Microbial profiling using 16S rRNA gene sequencing revealed the presence of phylogenetically novel taxa at various taxonomic levels, spanning from genera to phyla. Many sequences belonged to novel classes within the phyla Hydrothermae, Altiarchaeota, Verrucomicrobia, and TA06. Cultivation-based methods employing oligotrophic media resulted in the isolation of 44 unique bacterial isolates. These include strains that withstand concentrations of up to 12% NaClw/v in cultivation media or survive a temperature of 100 °C, as well as hitherto uncultured bacterial species belonging to the genera Thermomonas, Paenibacillus, and Cellulomonas. These isolates harbored stress response genes that allow them to thrive in the extreme environment of thermal springs. CONCLUSIONS: Our study is the first to analyze the overall microbial community composition of the renowned Karlovy Vary thermal springs. We provide insight into yet another level of uniqueness of these springs. In addition to their unique health benefits and cultural significance, we demonstrate that these springs harbor phylogenetically distinct microorganisms with unusual life strategies. Our findings open up avenues for future research with the promise of a deeper understanding of the metabolic potential of these microorganisms.
Keywords: Thermal water springs; Amplicon sequencing analysis; Cultivation analysis; Phylogenetic novelty